Redescription of Neotyphloceras chilensis Jordan, new status (Siphonaptera: Ctenophthalmidae: Neotyphloceratini) - Sanchez, Juliana; Amor, Verónica; Bazán-León, Enrique A.; Vásquez, Rodrigo A.; Lareschi, Marcela (Zootaxa, 2012)
Neotyphloceras crassispina chilensis Jordan is elevated to species status based on comparison of its morphology withother species and subspecies of the genus. Neotyphloceras chilensis is redescribed from specimens from Region IV of Coquimbo, Chile. A key for identification of species and subspecies of Neotyphloceras is provided.